Range of refractive independence and mechanism of action of a corneal shape–changing hydrogel inlay: Results and theory. Issue 8 (August 2015) - Steinert, Roger F.; Schwiegerling, Jim; Lang, Alan; Roy, Adam; Holliday, Keith; Garza, Enrique Barragán; Chayet, Arturo S.
Abstract : Purpose : To demonstrate the independence of visual performance over a range of preoperative refraction and age in presbyopes implanted with a corneal shape–changing inlay (Raindrop Near Vision Inlay). Setting : Two multispecialty clinics, Monterrey and Tijuana, Mexico. Design : Prospective case series. Methods : The nondominant eyes of patients were implanted with the hydrogel corneal inlay beneath a femtosecond flap, centered on the pupil. Clinical outcomes included uncorrected near, intermediate, and distance visual acuity (UNVA, UIVA, and UDVA) and patient‐assessed task performance in good light and dim light. Statistical analyses assessed the dependencies on preoperative age (45 to 60 years) and preoperative manifest refraction spherical equivalent (MRSE) (−0.5 to +1.5 diopters [D]). Using the inlay effect derived from wavefront measurements, an eye model was created through which letter charts were simulated. Results : The study evaluated eyes of 188 patients. Postoperative UNVA, UIVA, and task performance at these distances in good light was independent of age and preoperative MRSE ( P > .05). Postoperative UDVA was weakly dependent on preoperative MRSE, but distance task performance in good light was not ( P > .05). In the treated eye, the mean postoperative UNVA was 20/25, UIVA was 20/25, and UDVA was 20/32. The clinical outcomes are explained by consideration of zones within the pupil generating good near, intermediate, and distance image quality. This was confirmed by visual acuity simulations. Conclusions : The continuous center‐near power profile induced by the corneal shape‐changing inlay provides good visual acuity and performance from distance through near over a 2.0 D range of preoperative refraction and presbyopic age. Financial Disclosure : Drs. Steinert, Schwiegerling, Barragán‐Garza, and Chayet are consultants to Revision Optics, Inc. Drs. Lang and Holliday and Mr. Roy are employees of Revision Optics, Inc. Drs. Steinert, Schwiegerling, Barragán‐Garza, and Chayet have no financial or proprietary interest in any material or method mentioned.